MENINGKATKAN KEMAMPUAN MOTORIK HALUS BAGI ANAK TUNAGRAHITA SEDANG MELALUI KEGIATAN MENENUN SEDERHANA KELAS IX/C1 DI SLB N.1 LIMAU MANIS PADANG - Sri Martayona (Universitas Negeri Padang, 2014)
Abstrack: This research was motivated by the problems found in the field, a child being X mental retardation experience obstacles in their fine motor skills ie stiffness in the muscles of his fingers. This makes the child difficult to perform daily activities. Under these conditions, this study aims to prove that a simple weaving activity can improve children's fine motor skills are being tunagrahita IX/C1 class at Limau manis N.1 SLB Padang This study used a single-subject design approach, with multiple cross design variables and data analysis techniques using visual analysis chart. Subjects were moderate mental retardation. Measurements using a variable frequency. Observations were made with two sessions: the first session Baseline (A) and intervention (B). Baseline observation carried seven times the data is stable and intervention as much as ten times the observational data varies, the observations from the baseline to the intervention on the child achieved a 3-7 variable, the second variable 2 -9, 3-5 third variable, the fourth variable 3-13, 3-7 fifth variable. Results from the baseline to the intervention increased. Based on the results of these studies concluded that the simple weaving activities can enhance fine motor skills in children tunagrahita were in SLB N 1 Padang Sweet Lemons. Teachers should be advised to use a simple weave activities for fine motor skills in children tunagrahita being. Kata kunci: menenun sederhana; motorik halus;tunagrahita sedang.